O-246 A drop in serum progesterone(P4) levels between 5th and 7th days of triggering ovulation is associated with lower ongoing pregnancy rate(OPR) in intrauterine insemination cycles. (30th June 2022) - Orhan, N; Gunalp, G.S; Yarali, H; Bozdag, G; Mumusoglu, S
Abstract: Study question: Is there any association between early- and mid-luteal phase serum P4 levels and OPR in patients undergoing IUI due to unexplained or mild male-factor infertility? Summary answer: A drop in serum progesterone (P4 ) levels between 5 th and 7 th day of triggering ovulation is independently associated with lower OPR in IUI cycles. What is known already: The definition of luteal phase insufficiency in natural cycles is controversial and might be encountered ∼10% of infertile couples. Serum P4 level measurement is a still the most feasible method for luteal phase monitoring. Recently, some research groups have been focusing on monitoring luteal phase in in-vitro fertilization cycles, however, there is scarce of evidence on luteal phase characteristics and reproductive outcomes in IUI cycles. Study design, size, duration: A prospective cohort study. A total of 179 consecutive patients (230 cycles) with unexplained and mild male factor infertility undergoing IUI treatment at Hacettepe University in between June 2020 and May 2021 were included. For ovarian stimulation, of the included 230 cycles, clomiphene citrate and gonadotropin were used consecutively in 161 cycles and only gonadotropin in the remaining 69 cycles. The primary outcome measure was the OPR. No progesterone was administered for luteal phase support. Participants/materials, setting, methods: Serum P4 levels were measured on the 5 th and 7 th day of hCG triggering.P4 level were available in 183 cycles for hCG+5 day, in 161 cycles for hCG+7 day. In order to investigate the effect of P4 levels on OPR, patients were divided into two groups as ≤ 10th percentile and >10th percentile according to serum P4 levels measured on hCG+5 and hCG+7 days, with the cut off values ≤5.6 ng/ml and ≤8.46 ng/ml, respectively. Main results and the role of chance: Of the 230 cycles 17 (7.4%) were resulted with ongoing pregnancy. In the univariate analysis, the OPRs of the hCG+5 and hCG+7 serum P4 ≤10% and >10% groups were 10.5% (2/19) versus 5.5% (9/164) (p = 0.80) and 0% (0/16) versus 7.5% (n = 11/145) (p = 0.24), respectively. There was no ongoing pregnancy in patient with ≤8.46 ng/ml serum P4 level on hCG+7 day. The ΔP4 value was calculated by subtracting the serum P4 level measured on hCG+5 from the serum P4 level measured on day hCG+7 (ΔP4 = hCG+7 – hCG+5). While none of the 26 patients with negative ΔP4 had ongoing pregnancy, 8 (6.2%) of 130 patients with positive ΔP4 had ongoing pregnancy (p = 0.194). In the multivariate-GEE (generalized estimating equation) analysis, ΔP4 was found to be an independent predictor of ongoing pregnancy alone (ß:0.137, 95% CI = 0.020-0.254, p = 0.02). Limitations, reasons for caution: The physiological circadian pulsatile secretion of P4 during the mid-luteal phase and limited sample size are limitations, however, blood sampling was standardized to reduce the impact of timing. Wider implications of the findings: Low progesterone level with the threshold ≤8.46 ng/ml on the hCG+7 day is associated lower OPR. Two measurements (hCG+5 day, hCG+7 day) of P4 may delineate those patients with a drop in P4, associated lower OPRs. Rescuing these IUI cycles with additional P4 supplementation should be tested in future randomized controlled trials. Trial registration number: NCT04707430